Non-relativistic quantum mechanics - Puri, Ravinder R. (Cambridge: Cambridge University Press, 2017)
"Introduces readers to non-relativistic quantum mechanics and its mathematical methods"--
History of quantum mechanics -- Vectors and operators -- Finite dimensional spaces -- Function space -- Postulates of quantum mechanics -- Density operator -- Measurement postulate and paradoxes of quantum mechanics -- Position and momentum representations -- Schrodinger equation in one dimension -- One-dimensional exactly solvable continuous potentials -- Partially and completely periodic potentials -- Harmonic oscillator -- Three-dimensional central potentials -- Symmetry in quantum mechanics -- Quantum theory of angular momentum -- Approximation methods -- Entanglement and local hidden variable theory.
Includes bibliographical references and index.
Keywords: Nonrelativistic quantum mechanics